Conversations with artificial intelligence about the key moments of healing of acute myocardial infarction - Iabluchankyi, Mykola (My University, 2023)
"This is our (MI&AI) 10-question conversations on current topics in the healing of acute myocardial infarction. It is interesting for me and I expect it will be interesting for you, both from a substantive point of view (the essence of the phenomenon of acute myocardial infarction (AMI), what it really is) and from the point of view of how AI approached understanding the natureof the problem problem and found the necessary solutions" (М. Iabluchankyi)
about the key moments of healing of acute myocardial infarction
Keywords: artificial intelligence; coronarogenic death; myocardial infarction